Clinical and Molecular Risk Factors for Recurrence Following Radical Surgery of Well-Differentiated Pancreatic Neuroendocrine Tumors - Pulvirenti, Alessandra; Pea, Antonio; Chang, David K.; Jamieson, Nigel B. (Frontiers in Medicine, 2020)
Well differentiated pancreatic neuroendocrine tumors are increasingly diagnosed neoplasms. For localized disease, surgery is the first-line therapy and is curative in most cases. However, although recurrence is a rare event, it can still occur up to 10 years from surgery worsening the prognosis. Many clinical and pathological factors have been associated with recurrence, however, it is currently unclear how to accurately discern patients at risk for relapse of disease from those that should be considered cured. In this review, we focus on clinical, pathological and molecular factors associated with recurrence and discuss available prediction tools to assess the risk of recurrence following surgery.